Sejarah Sosial Teori Hukum Islam Mazhab Maliki - Arif, Miftakhul (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2024)
The Maliki school of thought has made a major contribution to the development of Islamic legal theory (usul al-fiqh). However, there has not been much research that has paid serious attention to the dynamics of the Islamic legal theory that developed in the Maliki School. This research aims to analyze the Maliki School of Islamic legal theory from a socio-historical perspective. This library research places the work of usul al-fiqh written by Malikiyah scholars as the primary data source. Meanwhile, secondary data sources were obtained from various other works that are relevant to the study topic. This research found that the Maliki School of Islamic legal theory developed dynamically because it was influenced by the social context. In the early of the formative period, the Maliki School was known as ahl al-atsar (textualists) because of its preference for the sunnah as a source of Islamic law. However, in subsequent developments, Malikiyah scholars became increasingly rationalist with a tendency to use ra'y with various variants (al-maslahat al-mursalah, istihsan, etc.) which relied on maqashid al-shari'ah in efforts to discover Islamic law.